Feasibility of a problem-based social constructivism learning model to improve higher-order thinking skills among primary school students - Sarnoko; Asrowi; Gunarhadi; Usodo, Budi (Journal of Education and e-Learning Research, 2024)
This research aims to demonstrate the results of an experiment on how the Problem-Based Social Constructivism Learning Model (PBSCL) can be developed to effectively promote Higher-Order Thinking Skills (HOTS) among primary school children. The methodology employed in this study was developmental research which involved thorough preliminary studies, meticulous product development and comprehensive product testing stages. Respondents for this study included model experts, language experts, content specialists and practitioners. Data collection instruments used were detailed questionnaires served during the feasibility test. In addition, product testing involved rigorously confirming the findings of product development through extensive expert validation, including learning model expert validation, content or material expert validation, language expert validation and practitioner validation. The results of the assessment on learning design expert validators for the PBSCL learning model indicated that they had high qualifications with the average score being 3.29. Consequently, learning design experts ensured that the criteria were meticulously met by the PBSCL learning model for HOTS improvement. Additionally, subject matter specialists confirmed the appropriateness and effectiveness of using the PBSCL learning model for HOTS improvement. The findings suggest that the PBSCL learning model has significant potential to substantially enhance HOTS among primary school students. However, further investigation is needed to fully validate its effectiveness and practical application in diverse educational settings.